VARIATION OF BIOMASS IN GRASSES GROWING IN WATER HABITAT BETWEEN INLAND SWAMP AND LAND - Louisa, Virgina Maria; Krisdianto, Krisdianto; Mahrita, Mahrita (TROPICAL WETLAND JOURNAL, 2016)
Grasses (family Poaceae), which belong to the weeds growing in water habitat between inland swamp and land, have the ability to survive the inland swamp environment that is inundated and poor in nutrients due to acidic soil. Lowland between inland swamp and land experiences waterlogging condition that changes over time from a puddle of water, which is very high in the rainy season, to ebb, becoming dry especially during the dry season. The objective of this study was to find out the variation of biomass in some grasses growing in water habitat between inland swamp and land. The study was conducted from April to July 2009 in Banjar Regency, South Kalimantan, at the villages of Tungkaran, Sungai Rangas, Penggalaman, and Sungai Tabuk. The analysis of samples was carried out at the Basic Laboratory of Faculty of Mathematics and Natural Siences, Lambung Mangkurat University Banjarbaru. There were seven stations, which were determined purposively, with three plot replications; the smallest plot was 20 x 20 cm. Three types of grass samples were taken and measured for individual height, wet weight, dry weight, moisture content and ash content. Measurements of the environmental parameters included the pH of soil and water, and the analysis of total N, P, and K. The average dry weight biomass of Hymenachne amplexicaulis, Brachiaria plantaginea, and Brachiaria mutica ranged from 1,135.18 to 2,556.80 gm-2, 1,854.88 to 2,480.63 gm-2, and 1,353.98 to 3,204.9 gm-2, respectively. These results indicate that the grasses growing closer to land, namely Brachiaria plantaginea and Brachiaria mutica, have higher biomass than the one growing a bit far from the land, namely Hymenachne amplexicaulis.